The Possibility of China's Industrial Park Management Committee to Promote Interenterprise Cooperative Innovation in the Park: A Trilateral Evolutionary Game Perspective. (6th October 2020) - Guo, Zhuopin; Zhen, Jie; Qu, Yiying; Ren, Hao
Abstract : Under China's distinct policy-driven agglomeration approach, the Chinese industrial park displays a low degree of industrial relevance and weak cooperation among enterprises in the park. The key to solving this problem lies in the guiding role of the park management committee. Accordingly, this study constructs a trilateral evolutionary game model of interenterprise cooperative innovation inside the industrial park under the supervision of the park management committee, leadership of the core enterprises, and with the participation of the small- and medium-sized enterprises. Through simulation analysis, this study explores the influencing factors behind the trilateral cooperative innovation strategy choices. Results show that (1) the park management committee, core enterprises, and small- and medium-sized enterprises have different degrees of influence on each other's willingness to participate in cooperative innovation; (2) small- and medium-sized enterprises are sensitive to the management committee's policy support, and core enterprises are sensitive to the management committee's financial support; (3) core enterprises are more sensitive to penalties and income distribution than small- and medium-sized enterprises; (4) the degree of resource complementarity and trust among enterprises has a profound effect on core enterprises and small- and medium-sized enterprises' willingness to participate in cooperative innovation.